2008
DOI: 10.1186/1617-9625-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial and fungal components in tobacco and tobacco smoke

Abstract: The microbiological composition of tobacco products was studied using culture and chemical analysis (of tobacco leaves) or chemical analysis only (tobacco and tobacco smoke). The chemical analyses utilized gas chromatography-tandem mass spectrometry for determining 3-hydroxy fatty acids, muramic acid, and ergosterol as markers of respectively lipopolysaccharide (LPS), peptidoglycan, and fungal biomass. Mesophilic bacteria dominated in both fresh and cured tobacco leaves; a range of additional bacteria and fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 14 publications
7
68
0
3
Order By: Relevance
“…In a comparison of the frequency of risk factors in the low-and middle-income groups, exposure to cigarette smoke (24) was observed more often in low-income families (Supplemental Table 3). Only age and number of siblings under the age of 14 years living at home influenced the severity of RSV bronchiolitis (Supplemental Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of the frequency of risk factors in the low-and middle-income groups, exposure to cigarette smoke (24) was observed more often in low-income families (Supplemental Table 3). Only age and number of siblings under the age of 14 years living at home influenced the severity of RSV bronchiolitis (Supplemental Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this concept, we and others [17,23,41,42] have shown that cigarette smoke modulates TLR2 and TLR4 expression. In addition, CSE contains LPS [43] which is a potent activator of TLR4 signalling. Using a neutralising antibodies against TLR4 and TLR2, we have shown a partial involvement of TLR4 in CSE-induced CXCL8 expression in primary human neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Mesophilic bacteria have been found in both fresh and cured tobacco leaves. A range of additional bacteria and fungi have been found in minor amounts; moreover, storing cigarettes at high humidity results in elevated levels of fungi in the cigarette tobacco, leading to increased ergosterol concentrations in the smoke [14]. In addition, the bacterial metagenome of a cigarette-based study revealed 15 different classes of bacteria and a broad range of potential pathogens (Acinetobacter, Bacillus, Burkholderia, Clostridium, Klebsiella, Pseudomonas aeruginosa, Serratia, Campylobacter, Enterococcus, Proteus and Staphylococcus) [15,16].…”
Section: Effect Of Cigarette Smoke Exposure On the Human Respiratory mentioning
confidence: 99%